La mujer ebria en Jan Steen, pintor barroco holandés, ¿una imagen ovidiana? - Díaz Gito, Manuel Antonio (2020)
El autor sugiere la posible relación entre un motivo frecuente en la pintura del artista barroco flamenco Jan Steen (1626-1679), la mujer ebria, y un pasaje de Ovidio donde el poeta elegíaco critica este tipo de comportamiento en las mujeres (ars 3,761-768).
The author of this article suggests the possible relation between the frequent motif of the drunken woman in the art of the Dutch Baroque painter Jan Steen (1626-1679) and a fragment from Ovid’s poetry (ars 3,761-768), where the Roman elegiac poet criticises this kind of behaviour in women.
Keywords: Steen, Jan, -- 1626-1679; Arte barroco; Poesía elegíaca